Theories, Techniques, Methods and Approaches of Second Language Acquisition: a Psychological Perspective - Delbio, A; Ilankumaran, M (International Journal of Engineering and Technology, 2018)
Psychological aspects play an important role in language learning. Motivation is one of the terms used to achieve the language. The theories of second language focus mainly on motivation, nature of motivation, implications of second language acquisition and linguistic process. The theories are practices and used as a teaching method. The instructor can have a clear vision on theories to implement them in the classroom. The learning environment and reinforcement are the important factors in learning psychology. Due to psychological problems and lack of training and guidance, the learners lose hope of learning. Cognitive psychology deals with mental process which involves in language learning. This paper aims at analysing the psychological factors affecting language acquisition and analyses the psychological theories, techniques, methods and approaches to develop the language acquisition.Â